Anspruch und Realität einer geplanten Hauptstadt: Islamabad in Pakistan - Kreutzmann, Hermann (ERDKUNDE, 1992)
The phenomenon of founding new capital cities characterizes a number of decolonized countries in Asia, Africa and Latin America. This paper discusses the case of Islamabad, the capital of Pakistan, which was founded 30 years ago. The expectations laid down in the complex dynapolis concept by the Creek town planner C . D. Doxiadis are compared with the present-day appearance and problems of Islamabad. The modernistic and westernized architectural euphoria of the 1960s has found its expressions in the city of Islam where hardly any elements of Islamic building traditions have been incorporated. The development of Islamabad is traced from the planning stages when the capital functions where transferred from the interim capital and industrial centre Karachi to Islamabad, the city of bureaucrats and diplomats. In the confrontation of plan with reality the emphasis is placed on three aspects of urban dwelling, i. e., habitation, transportation, and supply situation. The existence of squatter settlements and mudhouse quarters prove the misconception of the town planners and the Capital Development Authority regarding the planning and provision of adequate accomodation to all social groups working and living in the capital. The inadequate traffic concept has omitted a public transport system that would allow commuting between different sectors of the capital. The inflexible hierarchical structure of shopping areas assigned to different residential quarters failed to serve the needs of the majority of the urban population. Periodic markets have been filling the supply gap and serve as dynamic business centres. Thirty years after its inception the appearance of Islamabad has deviated in many respects from the town planning concept and reflects overall socioeconomic developments within Pakistan.